2006
DOI: 10.1063/1.2210972
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oriented nanofibers using electrospinning

Abstract: This letter reports on a simple, easy method for generating suspended nanofibers on a dielectric substrate using various target electrodes. By controlling the electrostatic field between the target electrodes, the nanofibers can be oriented to the electric field direction at the electrodes. The alignment of nanofibers was dependent on the applied frequency, field strength, and shape of the electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…The detailed function and computer-simulated results of the auxiliary electrode are described elsewhere. 8,9 The guiding electrodes are very important in electrospinning material for wound dressings to ensure that the electrospun fibers are deposited stably on the desired target plate. Figure 2 shows high-speed photographs of electrospun ultrafine fibers going past the guiding electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed function and computer-simulated results of the auxiliary electrode are described elsewhere. 8,9 The guiding electrodes are very important in electrospinning material for wound dressings to ensure that the electrospun fibers are deposited stably on the desired target plate. Figure 2 shows high-speed photographs of electrospun ultrafine fibers going past the guiding electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…[1,[18][19][20] Two conductive strips separated by a gap of few centimeters were used as collector, thus forcing the fibers to align themselves perpendicular to each edge of the gap (Figure 1 b). The resulting fibers turned out to be strongly aligned.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] Subsequently, the use of an array of parallel strip electrodes was developed to increase the size of the electrospun membrane. [15] Regarding this parallel electrode approach, it is reported that the dielectric property of the electrodes can strongly affect the degree of alignment. [16] According to theoretical and experimental studies, the gap size is also a critical parameter that influences the membrane morphology.…”
Section: Introductionmentioning
confidence: 99%